SINTESIS LiBOB DAN ANALISA STRUKTUR KRISTALNYA [Synthesis and Analysis Crystalline Structure LiBOB] - Wigayati, Etty Marti (Jurnal Metalurgi, 2015)
Lithium Bis (Oxalato) Borate(LiBOB) as lithium salt that is currently being developed as an alternative electrolytes for Li - Ion battery, LiBOB electrolyte is considered more environmentally friendly, LiBOB also have a fairly high heat stability which is equal to 302 °C.This research aims to synthesize LiBOB thento determine the crystal structure and the optimum duration of sintering.At present work, the synthesis of Lithium Bisoxalato Borate (LiBOB) was done by solid-state reaction method. The raw materials was mixed homogeneously. These samples were calcinated at 120 °C for about 2 hours then sintered at 240 °C with various durations (2, 3, and 4 hours). XRD characterization was done for identifying phases. From XRD interpretation, there are LiBOB Hydrate and other impurities at two-hour sintered sample. There are LiBOB Hydrate and H,BO, at three-our sintered sample. There are LiBOB, LiBOB Hydrate, and other impurities at four-hour sintered sample. The sample with 240 °C/4 hour parameter is the most optimum sample based on the convergention to the LiBOB and LiBOB Hydrate phases at standard commercial LiBOB sample (Sigma Aldric). The crystal system of the LiBOB phase is orthorombic with lattice parameters a = 5.74 A, b = 6.79 A, c = 14.45 A, a = B = y = 90°, space groupPnma (62), and FoM 1.386. On the other hand, the crystal system of LiBOB Hydrate phase is also orthorombic with lattice parameters a = 16.119 A, b = 15.913 A, c = 5.6182 A, a = B = y = 90°, space group Pbca (61), and FoM 0.824.